Highlight on the Mathematical Modeling of Controlled Free Radical Polymerization - Mamdouh A. Al-Harthi (International Journal of Polymer Science)
Over the last quarter century, controlled free radical polymerization (CFRP) has received great attention by the researchers of polymer science and engineering. In addition to the experimental studies, many publications in the literature dealt with the modeling of CFRP processes. A review of acknowledged and well-received researches on mathematical modeling in the area of CFRP is presented in this work. Three main categories of CFRP (namely, ATRP, RAFT, and NMP) are taken into consideration in the review. The different techniques used in modeling CFRP processes are also enumerated with more emphasis on Monte Carlo simulation and the method of moments. The review provides a better understanding of the processes and the recent efforts to model CFRP.